Transcatheter versus surgical aortic valve replacement in intermediate‐risk patients: Evidence from a meta‐analysis. Issue 3 (11th April 2017) - Sardar, Partha; Kundu, Amartya; Chatterjee, Saurav; Feldman, Dmitriy N.; Owan, Theophilus; Kakouros, Nikolaos; Nairooz, Ramez; Pape, Linda A.; Feldman, Ted; Dawn Abbott, J.; Elmariah, Sammy
Abstract : Objectives: We performed a meta‐analysis to evaluate the efficacy and safety of transcatheter aortic valve replacement (TAVR) in comparison to surgical aortic valve replacement (SAVR) in intermediate‐risk patients. Background: TAVR is an established treatment option in high‐risk patients with severe aortic valve stenosis (AS). There are fewer data regarding efficacy of TAVR in intermediate‐risk patients. Methods: Databases were searched through April 30, 2016 for studies that compared TAVR with SAVR for the treatment of intermediate‐risk patients with severe AS. We calculated summary risk ratios (RRs) and 95% confidence intervals (CIs) with the random‐effects model. Results: The analysis included 4, 601 patients from 7 studies (2 randomized and 5 observational). There was no significant difference in all‐cause mortality between the two groups after mean follow‐up of 1.15 years [14.7% with TAVR vs 15.4% with SAVR; RR 0.93; 95% CI 0.77–1.12]. TAVR resulted in lower rates of acute kidney injury [number needed to treat (NNT) = 26], major bleeding (NNT = 4), and atrial‐fibrillation (NNT = 6), but higher rates of major vascular complications [number needed to harm (NNH)= 18], and moderate/severe aortic regurgitation (NNH = 13). The rate of permanent‐pacemaker implantation was significantly higher with TAVR in observational studies (RR 2.31; 95% CI 1.22–2.81), but not in RCTs (RR 1.21; 95% CI 0.93–1.56). No significant difference in the rate of stroke or myocardial infarction was observed. Conclusions: Our analysis of mid‐term results showed that TAVR has similar clinical efficacy to SAVR in intermediate‐risk patients with severe AS, and can be a suitable alternative to surgical valve replacement. © 2017 Wiley Periodicals, Inc.